The impact of digital infrastructure on the synergistic effects of urban pollution and carbon reduction: empirical evidence from China - Li, Fanglin; Diao, Ziyu (Frontiers in Environmental Science, 2025)
Digital infrastructure, as a core component of new infrastructure, plays a powerful engine role in driving urban development. It not only profoundly shapes the future landscape of cities but also plays an irreplaceable role in accelerating the dual transition of industries toward digitization and greening. This process not only promotes the deep integration and synergistic development of urban digitization and greening but also cleverly builds a bridge for the dual benefits of pollution reduction and carbon reduction, laying a solid foundation for achieving an environmentally friendly and resource-saving society. This study adopt a multifaceted approach to explore the impact of digital infrastructure on the synergistic management of urban pollution abatement and carbon reductions. The coefficient for this effect was statistically significant at a 1% significance level (0.1056), demonstrating its capacity to support reductions in both pollution and carbon emissions, with regional variations observed. Furthermore, examining factor flows reveals that digital infrastructure promotes enhanced labor, capital, and innovation flows. Notably, the impact of digital infrastructure on these sectors exhibited coefficients of 57.5616, 0.0097, and 0.0189 respectively. These findings point to a significant nexus between digital infrastructure and sustainable urban development. A nonlinear U-shaped relationship was observed between digital infrastructure and the joint effect of both pollution mitigation and carbon reduction. This study concludes with policy recommendations aiming to optimize the utilization of digital infrastructure for achieving sustainable urban development goals.